Sugars in Multicomponent Reactions: A Toolbox for Diversity-Oriented Synthesis - Maikhuri, Vipin K.; Verma, Vineet; Chaudhary, Ankita; Mathur, Divya; Kumar, Rajesh; Prasad, Ashok K. (Synthesis, 2023)
Multicomponent reactions (MCRs) cover strategically employed chemical transformations that incorporate three or more reactants in one pot leading to a functionalized final product. Thus, it is an ideal tool to achieve high levels of complexity, diversity, yields of desired products, atom economy, and reduced reaction times. Sugars belong to the class of naturally occurring compounds with fascinating applications in the field of drug discovery due to the presence of various hydroxy groups and well-defined stereochemistry. However, their potential in MCRs has been realized only recently. This account describes recent advances in the synthesis of sugar-derived heterocycles synthesized by MCRs. We hope to encourage the synthetic and medicinal chemistry community to apply this powerful MCR chemistry to generate novel glycoconjugate challenges.1 Introduction2 Synthesis of Various Functionalized Sugar Compounds2.1 Passerini and Ugi Multicomponent Reactions2.2 Petasis Reaction2.3 Hantzsch Reaction2.4 Domino Ferrier–Povarov Reaction2.5 Marckwald Reaction2.6 Groebke–Blackburn–Bienaymé (GBB) Reaction2.7 Prins–Ritter Reaction2.8 Debus–Radziszewski Imidazole Synthesis Reaction2.9 Mannich Reaction2.10 A3-Coupling Reaction2.11 [3+2]-Cycloaddition Reactions2.12 Miscellaneous Reactions3 Conclusion
Keywords: sugars; multicomponent reactions; isocyanides; aldehydes; domino reactions